The cranes are flying - Rozov, Viktor Sergeevič 1913-2004; Weinberg, Mieczysław 1919-1996 (<<The>> Criterion Collection, 2020)
"Die Geschichte einer vom Krieg zerrissenen Liebe: Veronika läßt sich von dem intellektuellen Bruder ihres Verlobten, einem Drückeberger, verführen, während Boris an der Front stirbt. Der sensibel gestaltete Film des vormaligen Dokumentaristen Kalatosow war einer der wenigen Welterfolge des sowjetischen Kinos der 50er Jahre. Seine Wirkung verdankt er vor allem seiner selbstkritisch-patriotischen Sicht bei nur geringer politischer Lehrhaftigkeit sowie der wunderbaren Kameraarbeit." [filmdienst.de]
Original: Sowjetunion 1957
Blu-ray special edition features: new 2K digital restoration, with uncompressed monaural soundtrack ; new interview with scholar Ian Christie on why the film is a landmark of Soviet cinema ; audio interview from 1961 with director Mikhail Kalatozov ; Hurricane Kalatozov, a documentary from 2009 on the Georgian director’s complex relationship with the Soviet government ; segment from a 2008 program about the film’s cinematography, featuring original storyboards and an interview with actor Alexei Batalov ; interview from 2001 with filmmaker Claude Lelouch on the film’s French premiere at the 1958 Cannes Film Festival ; new English subtitle translation ; plus: An essay by critic Chris Fujiwara
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc